A MoS2 / graphene / Mxene composite film and preparation method thereof

MoS2/graphene composite film was prepared by lithium ion intercalation method and electrospinning technology, and Mxene material was electrostatically sprayed on its surface at high pressure, which solved the problem of insufficient complexity and performance of the preparation of flexible lithium battery films in the prior art, and achieved the goal of realizing the It is a composite film with controllable thickness, excellent electrochemical performance and stable mechanical performance.

CN115132990BActive Publication Date: 2025-02-18JIANGSU UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210782154.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-04
Publication Date
2025-02-18
Estimated Expiration
2042-07-04

AI Technical Summary

Technical Problem

In the prior art, when preparing flexible lithium battery films, there are problems such as complex preparation methods, difficult to control thickness, poor electrochemical performance and unstable mechanical properties.

Method used

The MoS2/graphene composite film was prepared by lithium-ion intercalation method and electrospinning technology, and Mxene material was added through high-voltage electrostatic spraying method to form a porous structural frame to improve conductivity and mechanical properties.

Benefits of technology

The MoS2/graphene/Mxene composite film with controllable thickness, excellent electrochemical performance and stable mechanical properties were achieved, reducing production costs and simplifying the assembly process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115132990B_ABST
    Figure CN115132990B_ABST
Patent Text Reader

Abstract

The invention discloses a MoS2 / graphene / Mxene composite film and a preparation method thereof. The film has MoS2 and graphene as the film body, and graphene and Mxene as the film coating. The preparation method comprises: preparing a single-layer MoS2 nanosheet, preparing an electrospinning solution of a single-layer MoS2 nanosheet and graphene, preparing a MoS2 / graphene composite film by electrostatic spinning, and obtaining a MoS2 / graphene / Mxene composite film by high-voltage electrostatic spraying. The MoS2 / graphene / Mxene composite film prepared by the invention is thin, light, flexible, and bendable, has a controllable thickness, is easy to assemble, and has excellent electrical conductivity, and can realize efficient circulation of lithium batteries. The preparation method adopts electrostatic spinning and electrostatic spraying technology, and has the advantages of good composite effect, simple process, high preparation efficiency, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a film and a preparation method thereof, and in particular to a MoS2 / graphene / Mxene composite film and a preparation method thereof. Background Art

[0002] In the pursuit of fashion and convenient lifestyles, people's demand for flexible electronics and wearable devices has increased significantly. Flexible electronics are developing in the direction of being portable, bendable, efficient, low-cost and recyclable. The existing conventional electrodes prepared by coating slurry on metal current collectors cannot meet the fashion needs of flexible electronic devices due to their inherent non-flexible electrode structure. The development of thin and light flexible electronics with bending stability has become a difficult point in the research of energy storage.

[0003] The patent with publication number CN105633344 discloses a flexible lithium battery film negative electrode material of molybdenum disulfide / nanocellulose / carbon nanotube / graphene composite, wherein the negative electrode material uses nanocellulose as a flexible substrate, and molybdenum disulfide nanosheets, graphene nanosheets and carbon nanotubes are mixed evenly and buried in the network of the nanocellulose to form a flexible self-supporting film electrode material with a dense network structure, wherein the composition and percentage of the film negative electrode material are respectively: 60-80wt% of molybdenum disulfide nanosheets, 10-30wt% of nanocellulose, 5-20wt% of carbon nanotubes, and 5-20wt% of graphene. The method of the present invention can reasonably and efficiently utilize the renewable energy of cellulose, without using metal aluminum foil and copper foil as current collectors, and without using fluorine-containing polymers as adhesives, thereby greatly avoiding the impact and harm on the ecological environment; the electrode obtained by the method of the present invention does not need to be pressed, but can be directly pressed and assembled, with high efficiency, and has good mechanical flexibility and continuous bending stability. However, this patent has shortcomings in the preparation method. The composite film prepared by this method is a wet film, which needs to be dehydrated under a pressure of 1MPa. The wet film after dehydration is sandwiched between two glass plates and dried to obtain a flexible lithium battery film negative electrode material of 20 to 30μm. There may be limitations in preparing a thickness of 100μm and above by this method. In addition, the prepared negative electrode material needs to be carbonized by high-temperature heat treatment. The film negative electrode material with a thickness of 20 to 30μm prepared by this method will curl up during the high-temperature heat treatment process, thereby affecting the performance of lithium-ion batteries. In addition, this patent uses nanocellulose as a fiber mechanical skeleton and binder, and it accounts for a relatively large proportion. It is well known that humidity can cause uncontrollable deformation and mechanical degradation of nanocellulose. During the drying process of the wet film obtained in this patent, this will seriously affect the mechanical properties of the electrode material. At the same time, this patent uses filter pressing and extrusion to prepare the film. Although a certain small thickness can be controlled, the relative volume is large, which will result in a low energy density per unit volume. Therefore, the electrode material prepared by this patent has poor electrochemical performance, thickness limitations and poor practicality. Summary of the invention

[0004] Purpose of the invention: In order to solve the technical problems existing in the prior art, the present invention aims to provide a MoS2 / graphene / Mxene composite film with a simple preparation method, controllable thickness and excellent electrochemical properties. The present invention also provides a preparation method thereof.

[0005] Technical solution: The MoS2 / graphene / Mxene composite film described in the present invention has MoS2 and graphene as the film main body, and graphene and Mxene as the film coating.

[0006] Furthermore, the graphene is graphene oxide.

[0007] The method for preparing the MoS2 / graphene / Mxene composite film of the present invention comprises the following steps:

[0008] (1) using a lithium ion intercalation method to react the lithium element of n-butyl lithium as an intercalation agent with bulk MoS2 in an n-hexane solution, performing ultrasonic treatment in a high-purity argon atmosphere, and after sufficient mixing, adding pre-deoxygenated ultrapure water and continuing ultrasonic treatment to obtain exfoliated MoS2 nanosheets, centrifuging the MoS2 nanosheets with anhydrous ethanol and ultrapure water in turn, removing the supernatant, retaining the bottom product, and repeating the centrifugation step to obtain a single-layer MoS2 nanosheet;

[0009] (2) taking graphene and the single-layer MoS2 nanosheets obtained in step (1) and ultrasonically dispersing them in anhydrous ethanol respectively, then mixing and ultrasonicating them, adding a high molecular polymer after sufficient mixing, continuing to stir, and obtaining a mixed solution of the single-layer MoS2 nanosheets and graphene after sufficient mixing;

[0010] (3) using the mixed solution obtained in step (2) as an electrospinning solution to perform electrospinning, and the obtained fiber film is vacuum dried and then heat treated in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film;

[0011] (4) Mixing the suspension of graphene and Mxene and subjecting it to ultrasonic treatment to obtain a graphene / Mxene precursor solution, spraying the graphene / Mxene precursor solution onto the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying, and subjecting it to ultraviolet light irradiation and reduction treatment to obtain a MoS2 / graphene / Mxene composite film.

[0012] Furthermore, in the step (1), the ultrasonic treatment is carried out in a high-purity argon atmosphere for 2 to 4 hours, the ultrasonic treatment is continued for 40 to 60 minutes after adding pre-deoxygenated ultrapure water, and the centrifugation step is repeated 10 to 25 times.

[0013] Furthermore, in the step (2), the mass ratio of single-layer MoS2 nanosheets to graphene is 1 to 2:1, the amount of solvent used is 5 to 15 ml, the time for ultrasonic dispersion in the solvent is 20 to 40 min, the time for continued ultrasonic mixing is 10 to 20 min, the stirring time after adding the polymer is 20 to 40 min, the polymer is one or more of PVP, PAN or PHBV, and the mass ratio of the polymer to the single-layer MoS2 nanosheets is 3 to 8:1.

[0014] Furthermore, in the step (3), the process parameters of electrospinning are: voltage of 10-20 kV, syringe needle nozzle diameter of 0.8-1.5 mm, curing distance from nozzle to receiving screen of 10-20 cm, indoor temperature of 15-25 ° C, relative humidity of 20-40%, and vacuum drying conditions of 60-80 ° C for 5-8 hours.

[0015] Furthermore, in the step (4), the mass ratio of graphene to Mxene is 1 to 2:1, the ultrasonic time after mixing is 20 to 40 minutes, the ultrasonic treatment is performed 2 to 4 times, and the process parameters of high-voltage electrostatic spraying are: the needle diameter is 0.8 to 1.5 mm, the voltage is 10 to 15 kV, the distance between the needle and the receiver is 5 to 15 cm, the spraying flow rate is 0.2 to 0.5 mL / min, the spraying time is 3 to 6 hours, and the reduction treatment time is 10 to 30 minutes.

[0016] Principle of the invention: The transition metal MoS2 used in the present invention has a high theoretical content and a higher theoretical redox potential, and has both an embedding type and a conversion reaction mechanism, but its conductivity is very poor, while graphene has excellent conductivity. Therefore, the conductivity and mechanical properties of the composite material are enhanced by the introduction of graphene. First, porous fibers are prepared by electrospinning. The material selection space is large, and the thickness can be controlled by the spinning time. There are a lot of gaps between the prepared composite fibers, which provide a buffer space for the volume change during the charge and discharge process; in addition, the composite fiber can shorten the Li + transmission distance, providing a larger electrolyte / electrode interface and more adsorbed Li for ion reactions during battery charging and discharging + Active sites form a three-dimensional conductive network inside the material. The carbon produced by the polymer in the composite fiber during the sintering process acts as a volume buffer skeleton, reducing the volume change of the material during the cycle and improving the conductivity of the material. Secondly, the graphene / Mxene material is sprayed on the composite fiber with high voltage electrostatic spraying, so that it can serve as a bridge between the composite fibers. The interconnected porous structure framework has good electronic conductivity, improves the flexibility of the membrane, and can provide faster ion channels and more abundant surface active sites during the charge and discharge process, providing abundant channels for the intercalation and deintercalation of lithium ions, thereby obtaining good electrochemical performance and cycle stability. Because the Mxene material has a large interlayer spacing, it provides sufficient buffer space for the lithium insertion-deintercalation process, and the layered structure provides fast ion channels.

[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0018] 1. The present invention combines electrospinning technology to prepare micron-level composite fibers, which have a wide range of material choices, and the thickness can be controlled by spinning time. There is a large amount of space between the fibers, which provides a buffer space for volume changes during charging and discharging. At the same time, the carbon produced by sintering the polymer acts as a volume buffer skeleton to reduce the volume change of the material during the cycle.

[0019] 2. The MoS2 / graphene / Mxene composite material prepared by the present invention can form good contact between graphene and MoS2 to reduce contact resistance. The larger interlayer spacing of Mxene provides sufficient buffer space for the lithium insertion-delithiation process. The larger interlayer spacing and abundant surface active sites of the composite material provide sufficient space for the volume expansion of MoS2 during the charge and discharge process. At the same time, the interconnected porous structure framework has good electronic conductivity, improves the flexibility of the membrane, and provides a continuous channel for rapid electron / ion transmission.

[0020] 3. The electrode material of the present invention is an electrode material with a self-supporting structure prepared without a conductive agent and a metal current collector, which reduces the production cost of the device and simplifies the battery assembly process. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an AFM image of a single-layer MoS2 nanosheet prepared in Example 1 of the present invention;

[0022] Figure 2 This is a SEM image of a single-layer MoS2 nanosheet prepared in Example 1 of the present invention;

[0023] Figure 3 TEM image of Mxene prepared in Example 1 of the present invention;

[0024] Figure 4 The cycle performance diagram of the MoS2 / graphene oxide composite film prepared in Example 1 of the present invention and the MoS2 / graphene oxide / Mxene composite film prepared in Comparative Example 2 at a current density of 50 mA / g;

[0025] Figure 5 This is the rate performance curve of the MoS2 / graphene oxide / Mxene composite film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments and drawings.

[0027] Example 1: The preparation method of the MoS2 / graphene / Mxene composite film is as follows:

[0028] (1) using a lithium ion intercalation method to react the lithium element of n-butyl lithium as an intercalation agent with bulk MoS2 in an n-hexane solution, and then ultrasonically treating it for 3 hours in a high-purity argon atmosphere. After sufficient mixing, adding pre-deoxygenated ultrapure water and continuing ultrasonication for 60 minutes to obtain exfoliated MoS2 nanosheets, centrifuging the MoS2 nanosheets with anhydrous ethanol and ultrapure water in turn, removing the supernatant, retaining the bottom product, and repeating the centrifugation step 25 times to obtain a single-layer MoS2 nanosheet;

[0029] (2) Graphene and the single-layer MoS2 nanosheets prepared in step (1) in a mass ratio of 1:1.5 were placed in 10 mL of anhydrous ethanol and ultrasonically dispersed for 30 min, then mixed and ultrasonicated for 20 min. After fully mixing, a polymer PVP and the single-layer MoS2 nanosheets were added in a mass ratio of 5:1, and stirring was continued for 30 min. After fully mixing, a mixed solution of MoS2 and graphene was obtained;

[0030] (3) Using the mixed solution obtained in step (2) as an electrospinning solution, electrospinning is performed, and the process parameters of electrospinning are: voltage of 16 kV, syringe needle nozzle diameter of 1.2 mm, curing distance from nozzle to receiving screen of 15 cm, indoor temperature of 20° C., and relative humidity of 25%. The vacuum drying conditions are: drying at 70° C. for 6 h. After vacuum drying, the obtained fiber film is heat-treated at 700° C. for 6 h in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film;

[0031] (4) Mix the graphene and Mxene suspension in a mass ratio of 1:1 and ultrasonicate for 30 minutes, perform ultrasonication 4 times to obtain a graphene / Mxene precursor solution, and spray the graphene / Mxene precursor solution on the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying. The process parameters of high-voltage electrostatic spraying are: needle diameter of 1.0 mm, voltage of 12 kV, distance between needle and receiver of 10 cm, spraying flow rate of 0.3 mL / min, spraying time of 4 h, and ultraviolet light irradiation reduction treatment for 20 min to obtain a MoS2 / graphene oxide / Mxene composite flexible self-supporting film.

[0032] See also Figure 1 and Figure 2 These are the AFM and SEM images of the few-layer MoS2 nanosheets prepared by the lithium ion intercalation method. It can be seen from the figure that MoS2 is a lamellar structure. The intercalation method can obtain exfoliated MoS2 nanosheets, and after multiple centrifugation, few-layer or single-layer MoS2 nanosheets can be obtained.

[0033] See also Figure 3 TEM image of Mxene, from which we can see that it is a thin single-layer structure.

[0034] Example 2: The preparation method of the MoS2 / graphene / Mxene composite film is as follows:

[0035] (1) using a lithium ion intercalation method to react the lithium element of n-butyl lithium as an intercalation agent with bulk MoS2 in an n-hexane solution, and then ultrasonically treating it in a high-purity argon atmosphere for 2 hours. After sufficient mixing, adding pre-deoxygenated ultrapure water and continuing ultrasonication for 40 minutes to obtain exfoliated MoS2 nanosheets, centrifuging the MoS2 nanosheets with anhydrous ethanol and ultrapure water in turn, removing the supernatant, retaining the bottom product, and repeating the centrifugation step 10 times to obtain a single-layer MoS2 nanosheet;

[0036] (2) Graphene and the single-layer MoS2 nanosheets prepared in step (1) in a mass ratio of 1:1 are placed in 5 mL of anhydrous ethanol and ultrasonically dispersed for 20 min, then mixed and ultrasonicated for 10 min. After sufficient mixing, the polymer PVP and PAN are added in a mass ratio of 3:1 to the single-layer MoS2 nanosheets, and stirring is continued for 20 min. After sufficient mixing, a mixed solution of MoS2 and graphene is obtained;

[0037] (3) Using the mixed solution obtained in step (2) as an electrospinning solution, electrospinning is performed, and the process parameters of electrospinning are: voltage of 10 kV, syringe needle nozzle diameter of 0.8 mm, curing distance from nozzle to receiving screen of 10 cm, indoor temperature of 15° C., and relative humidity of 20%. The vacuum drying conditions are: drying at 60° C. for 5 h, and the obtained fiber film is then heat-treated at 500° C. for 5 h in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film;

[0038] (4) Mix the graphene and Mxene suspensions in a mass ratio of 2:1 and ultrasonicate for 40 minutes. Ultrasonicate twice to obtain a graphene / Mxene precursor solution, and spray the graphene / Mxene precursor solution on the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying. The process parameters of high-voltage electrostatic spraying are: needle diameter of 0.8 mm, voltage of 10 kV, distance between needle and receiver of 8 cm, spraying flow rate of 0.2 mL / min, spraying time of 6 h, and ultraviolet light irradiation reduction treatment for 10 min to obtain the MoS2 / graphene / Mxene composite film.

[0039] Example 3: The preparation method of the MoS2 / graphene / Mxene composite film is as follows:

[0040] (1) using a lithium ion intercalation method to react the lithium element of n-butyl lithium as an intercalation agent with bulk MoS2 in an n-hexane solution, and then ultrasonically treating it in a high-purity argon atmosphere for 4 hours. After sufficient mixing, adding pre-deoxygenated ultrapure water and continuing ultrasonication for 50 minutes to obtain exfoliated MoS2 nanosheets, centrifuging the MoS2 nanosheets with anhydrous ethanol and ultrapure water in turn, removing the supernatant, retaining the bottom product, and repeating the centrifugation step 20 times to obtain a single-layer MoS2 nanosheet;

[0041] (2) Graphene and the single-layer MoS2 nanosheets prepared in step (1) in a mass ratio of 1:2 are placed in 15 mL of anhydrous ethanol and ultrasonically dispersed for 40 min, and then mixed and ultrasonicated for 15 min. After sufficient mixing, the polymer PVP and PHBV are added in a mass ratio of 8:1 to the single-layer MoS2 nanosheets, and stirring is continued for 40 min. After sufficient mixing, a mixed solution of MoS2 and graphene is obtained;

[0042] (3) Using the mixed solution obtained in step (2) as an electrospinning solution, electrospinning is performed, and the process parameters of electrospinning are: voltage of 20 kV, syringe needle nozzle diameter of 1.5 mm, curing distance from nozzle to receiving screen of 20 cm, indoor temperature of 25° C., and relative humidity of 40%. The vacuum drying conditions are: drying at 80° C. for 8 h. After vacuum drying, the obtained fiber film is heat-treated at 600° C. for 8 h in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film;

[0043] (4) Mix the graphene and Mxene suspension at a mass ratio of 1.5:1 and ultrasonicate for 20 minutes. Ultrasonicate for three times to obtain a graphene / Mxene precursor solution, and spray the graphene / Mxene precursor solution on the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying. The process parameters of high-voltage electrostatic spraying are: needle diameter of 1.5 mm, voltage of 15 kV, distance between needle and receiver of 15 cm, spraying flow rate of 0.5 mL / min, spraying time of 3 h, and ultraviolet light irradiation reduction treatment for 30 min to obtain the MoS2 / graphene / Mxene composite film.

[0044] Comparative Example 1: The difference from Example 1 is that in step (2), the mass ratio of graphene to single-layer MoS2 nanosheets is 3:1.

[0045] Comparative Example 2: The difference from Example 1 is that step (4) is not included.

[0046] The MoS2 / graphene / Mxene composite films prepared in Examples 1-3 and Comparative Examples 1-2 were applied to lithium batteries. The preparation method was as follows: a metal lithium sheet was used as a counter electrode, Celegard 2300 was used as a diaphragm, and a 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) solution was used as an electrolyte. A CR-2025 type simulated battery was assembled in a glove box filled with argon.

[0047] The CR-2025 type simulated battery was placed on an electrochemical working platform to test the electrochemical performance, and the performance test results are shown in Table 1. From the data in Table 1, it can be seen that the overall performance is: Example 1> Example 3> Example 2> Comparative Example 2> Comparative Example 1.

[0048] Comparing Example 1 with Comparative Example 2, the experimental results are shown in Figure 4 and Figure 5 , Figure 4 The figure is the 60 cycle performance graph of MoS2 / graphene composite material and MoS2 / graphene / Mxene composite material at a current density of 50mA / g. By comparing the cycle performance graph and rate performance curve of MoS2 / graphene composite material and MoS2 / graphene / Mxene composite material, it can be seen that after 60 cycles, MoS2 / graphene / Mxene composite material still has good reversible capacity. And from the rate curves at different current densities ( Figure 5 ) It can be seen that as the charge and discharge current density increases, the capacity of the composite material continues to decrease. When the current density returns to 50mA / g, the capacity recovers rapidly and remains at 950mAh / g. The addition of graphene and Mxene gives the composite material excellent conductivity. The high adsorption capacity graphene and Mxene materials have a large interlayer spacing and abundant surface active sites, providing sufficient space for the volume expansion of MoS2 during the charge and discharge process; under the synergistic effect of graphene and Mxene, more channels are further provided for the movement of ions, which greatly improves the lithium ion charge exchange rate and lithium ion embedding rate, thereby improving the overall electrochemical performance.

[0049] Table 1 Performance of MoS2 / graphene / Mxene composite films prepared in Examples 1-3 and Comparative Examples 1-2 when applied to lithium batteries

[0050]

Claims

1. A MoS2 / graphene / Mxene composite film, characterized in that: The film has MoS2 and graphene as the main body of the film, graphene and Mxene as the film coating, and the thickness of the film is 100-150 μm; the preparation method of the MoS2 / graphene / Mxene composite film includes the following steps: (1) The lithium element of n-butyl lithium is used as an intercalation agent to react with bulk MoS2 in an n-hexane solution, and ultrasonic treatment is performed in a high-purity argon atmosphere. After sufficient mixing, pre-deoxygenated ultrapure water is added and ultrasonic treatment is continued to obtain exfoliated MoS2 nanosheets. The MoS2 nanosheets are centrifuged with anhydrous ethanol and ultrapure water in sequence, the supernatant is removed, the bottom product is retained, and the centrifugation steps are repeated to obtain single-layer MoS2 nanosheets; (2) taking graphene and the single-layer MoS2 nanosheets obtained in step (1) and placing them in anhydrous ethanol for ultrasonic dispersion, mixing and continuing ultrasonication, after being fully mixed, adding a high molecular polymer, continuing stirring, and after being fully mixed, obtaining a mixed solution of the single-layer MoS2 nanosheets and graphene; (3) using the mixed solution obtained in step (2) as an electrospinning solution to perform electrospinning, and the obtained fiber film is vacuum dried and then heat treated in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film; (4) Mixing the suspension of graphene and Mxene and subjecting it to ultrasound to obtain a graphene / Mxene precursor solution, spraying the graphene / Mxene precursor solution onto the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying, and subjecting it to ultraviolet light irradiation and reduction treatment to obtain a MoS2 / graphene / Mxene composite film.

2. The composite film according to claim 1, characterized in that The graphene is graphene oxide.

3. A method for preparing the MoS2 / graphene / Mxene composite film according to claim 1, characterized in that: The following steps are involved: (1) The lithium element of n-butyl lithium is used as an intercalation agent to react with bulk MoS2 in an n-hexane solution, and ultrasonic treatment is performed in a high-purity argon atmosphere. After sufficient mixing, pre-deoxygenated ultrapure water is added and ultrasonic treatment is continued to obtain exfoliated MoS2 nanosheets. The MoS2 nanosheets are centrifuged with anhydrous ethanol and ultrapure water in sequence, the supernatant is removed, the bottom product is retained, and the centrifugation steps are repeated to obtain single-layer MoS2 nanosheets; (2) taking graphene and the single-layer MoS2 nanosheets obtained in step (1) and placing them in anhydrous ethanol for ultrasonic dispersion, mixing and continuing ultrasonication, after being fully mixed, adding a high molecular polymer, continuing stirring, and after being fully mixed, obtaining a mixed solution of the single-layer MoS2 nanosheets and graphene; (3) using the mixed solution obtained in step (2) as an electrospinning solution to perform electrospinning, and the obtained fiber film is vacuum dried and then heat treated in a tubular furnace in a nitrogen atmosphere to obtain a MoS2 / graphene composite film; (4) Mixing the suspension of graphene and Mxene and subjecting it to ultrasound to obtain a graphene / Mxene precursor solution, spraying the graphene / Mxene precursor solution onto the surface of the MoS2 / graphene composite film by high-voltage electrostatic spraying, and subjecting it to ultraviolet light irradiation and reduction treatment to obtain a MoS2 / graphene / Mxene composite film.

4. The preparation method according to claim 3, characterized in that: In the step (2), the mass ratio of graphene to single-layer MoS2 nanosheets is 1:1-2.

5. The preparation method according to claim 3, characterized in that: In the step (2), the high molecular weight polymer is one or more of PVP, PAN or PHBV.

6. The preparation method according to claim 3, characterized in that: In the step (2), the mass ratio of the high molecular weight polymer to the single-layer MoS2 nanosheet is 3 to 8:

1.

7. The preparation method according to claim 3, characterized in that: In the step (3), the process parameters of electrospinning are: voltage of 10-20 kV, syringe needle nozzle diameter of 0.8-1.5 mm, curing distance from nozzle to receiving screen of 10-20 cm, indoor temperature of 15-25 ° C, and relative humidity of 20-40%.

8. The preparation method according to claim 3, characterized in that: In the step (3), the fiber is heat treated in a tubular furnace in a nitrogen atmosphere at a temperature of 500-700° C. and a holding time of 5-8 hours.

9. The preparation method according to claim 3, characterized in that: In the step (4), the mass ratio of graphene to Mxene is 1-2:

1.

10. The preparation method according to claim 3, characterized in that: In the step (4), the process parameters of high-voltage electrostatic spraying are: needle diameter of 0.8-1.5 mm, voltage of 10-15 kV, distance between needle and receiver of 5-12 cm, spraying flow rate of 0.2-0.5 mL / min, and spraying time of 3-5 h.

Citation Information

Patent Citations

  • Preparation method of graphene / molybdenum disulfide composite fiber fabric

    CN114507981A

  • KR20190110056A